(untitled) (Pragyajyoti, 2024)
This research paper deals with how the protagonists of the ‘The Awakening’, ‘A Respectable Woman’ and ‘The Kiss’ try to escape from the reality in the name of freedom and right. The heroines desire to experience both wealth and liberation at once which seem barely possible. This drags them to commit adultery, to intrigue to taste the sexual liberty and baffle the loved one to enjoy the opulence. They are running away from one scenario to other only to fulfil their hidden desires. Either way, they seem to fail to perform their each responsibility as patriarchy becomes the obstacle to prove them wrong. Their awakening comes only by sacrificing their intimate relationships. Their awareness about the sense of self and sexuality weigh colossally which should be paid by the heroines by surrendering to the patriarchy. The theories of feminism and psychoanalysis are richly used in this paper to justify the reason behind the escaping of the protagonists.